9. Together in Death: Demography and Funerary Practices in Contemporary Multiple Internments in Irish Medieval Burial Grounds (AmS-Skrifter, 2019)
Contemporary multiple interment is a minority burial practice occasionally encountered in Medieval Christian burial grounds that is suggestive of the death of two or more individuals at the same time followed by a conscious decision by the living to bury those individuals together. The study reviews the evidence from thirty-one Irish burial grounds (spanning AD 300 to 1700) to explore the nature of the demographic combinations apparent in these contemporary multiple interments. Drawing upon information gleaned from contemporary historical sources, an attempt will be made to proffer possible scenarios to account for the different demographic configurations apparent in the burials. Funerary practices, in particular, positioning of the bodies, will be explored to see if insights can be gained concerning the nature of the potential social relationships that may have existed between those interred together in each grave. The findings from Ireland will be compared to those of studies of similar burials in Anglo-Saxon England.